Kinetics of the Acetyl Migration in Some Adducts of Acetyl-1,4-Benzoquinones: Part III† - Majeed Dabbagh, Abdul; Al-Hamdany, Raad (Asian Journal of Chemistry, 2010)
The Diels-Alder adducts of acyl-1,4-benzoquinones (enediones), I, undergo base induced rearrangement in ethanolic pyridines. The effects of pyridine moiety on the reaction rate were studied. The reaction rate was studied in different compositions of pyridine/ethanol in detail. Electronic and steric factors have great influence on the rate of rearrangement. The kinetic results are in full agreement with the proposed mechanism.